If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x = x + 7 + -4 Reorder the terms: -3x = 7 + -4 + x Combine like terms: 7 + -4 = 3 -3x = 3 + x Solving -3x = 3 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -3x + -1x = 3 + x + -1x Combine like terms: -3x + -1x = -4x -4x = 3 + x + -1x Combine like terms: x + -1x = 0 -4x = 3 + 0 -4x = 3 Divide each side by '-4'. x = -0.75 Simplifying x = -0.75
| 2x+3(x+1)=2(x+3)+7 | | 4/x-7/5x=-/12 | | 12-2(x-4)=3(x+2)-11 | | 7t-51=96 | | -8+y=9 | | 200x^2+300x-80=0 | | -9=w-7 | | 5-12/a=5/3 | | 6+b=38 | | 2y=8x+x+7 | | 12x-5+7x-5=180 | | 1/2x-9=-11 | | 4(3x+2)=-5(5x-2)+2x | | 20x+5=24-12x | | Y=log(-3x) | | 2x+3x+5x=y | | 5x+4=x+4(2+x) | | 60x+45=285 | | 3x+17=9-5x | | 9/25-y=-1/4 | | 8x-(2x-9)=4x-(8+4x) | | y-4-7y-3= | | .69x+19=43 | | y/4=5/13 | | 675x+125=3175 | | 3y^3-2y=x-3 | | 55x+850=123 | | y-1=2/3(x=9) | | x*10+12*8=196 | | 10=y+z | | x/2-=1 | | u/10=13/11 |